Clinical Functional MRI Presurgical Functional Neuroimaging - Stippich, Christoph (Diagnostic Imaging, 2015)
The second, revised edition of this successful textbook provides an up-to-date description of the use of preoperative functional magnetic resonance imaging (fMRI) in patients with brain tumors and epilepsies. State of the art fMRI procedures are presented, with detailed consideration of practical aspects, imaging and data processing, normal and pathological findings, and diagnostic possibilities and limitations. Relevant information on brain physiology, functional neuroanatomy, imaging technique, and methodology is provided by recognized experts in these fields. Compared with the first edition, chapters have been updated to reflect the latest developments and in particular the current use of diffusion tensor imaging (DTI) and resting-state fMRI. Entirely new chapters are included on resting-state presurgical fMRI and the role of DTI and tractography in brain tumor surgery. Further chapters address multimodality functional neuroimaging, brain plasticity, and pitfalls, tips, and tricks. The book is designed to be of value to beginners, trained clinicians, and experts alike.